Identifying pluralistic approaches in language subjects in Denmark, Norway, and Sweden - A comparative curriculum analysis - Drachmann, Natascha; Haukås, Åsta; Lundberg, Adrian (Language, Culture and Curriculum, 2023)
In Scandinavia, plurilingualism has been embraced as an important goal in language curricula. However, research shows that teachers struggle to understand what plurilingualism is and how it can be implemented. To address this lack of clarity, we analysed the curricula for the three main language subjects of schooling in Denmark, Norway, and Sweden with the purpose of identifying which pluralistic approaches can be found in them. We based our analysis on the three main approaches described in The Framework of Reference for Pluralistic Approaches to Languages and Cultures: integrated didactic approach (IDA), intercomprehension between related languages (ICRL) and eveil aux langues (EAL). We found several similarities across the Scandinavian countries, but also some major differences, suggesting that plurilingual education in these countries will likely have different learning outcomes for the students. For example, IDA is lacking in the Swedish curriculum, and the goals for ICRL are more ambitious in Denmark than in the other countries. Furthermore, Norway and Sweden include national minority languages in their pluralistic approaches, whereas no attention is given to language diversity in regions with close political bonds to Denmark, such as the Faroe Islands, Iceland, and Greenland.